Peran Media Massa dalam Mempengaruhi Public Trust di Masyarakat - Rina Ade Saputri; Laras Ayu Pratiwi; Erina Setianingrum (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2022)
Advances in Technology, Information and Communication (ICT) have an impact on the use of mass media in people's daily lives. This can form a separate character for the community. The characteristics of society can be seen from some of feedback given in the mass media. Through the mass media, the public can convey various opinions, complaints, criticisms, and suggestions regarding anything, therefore the mass media has an influence in society. The positive impact is felt, namely the easier access to information quickly, while the negative impact is felt, namely the easier access to information, of course, the public will be trapped in the spread of fake news (hoaks). The solution to this problem is to become a wise society in sorting, processing, and controlling what is received so that it does not become raw material that is consumed without knowing the truth. In this study using the literature review (literature review). The use of this method is based on analysis of literature studies, journals, articles, websites, and theses which are adapted to the related title. The purpose of this study was to identify and analyze the role of social media in influencing public trust in society.